2018
DOI: 10.5713/ajas.17.0443
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameter estimation for milk β-hydroxybutyrate and acetone in early lactation and its association with fat to protein ratio and energy balance in Korean Holstein cattle

Abstract: ObjectiveThe objective of this study was to estimate the genetic parameters for milk β-hydroxybutyrate (BHBA), acetone (Ac), fat protein ratio (FPR), and energy balance (EB) using milk test day records and investigate the effect of early lactation FPR and EB on milk ketone body concentrations.MethodsTotal 262,940 test-day records collected from Korea Animal Improvement Association during the period of 2012 to 2016 were used in this study. BHBA and Ac concentrations in milk were measured by Fourier transform in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
8
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 16 publications
4
8
3
Order By: Relevance
“…An exception to these reports was a higher heritability estimate reported by Buitenhuis et al (2013) for milk BHB (h 2 = 0.87) using cows that were all sampled in mid-lactation. The heritability value estimated in our study for milk acetone (h 2 = 0.10) was generally lower than estimates from previous studies, which were in the range of 0.22 to 0.31 (Lee et al., 2016; Ranaraja et al, 2018). Generally, heritability estimates for milk concentration of ketone bodies might vary between studies depending on stages of lactation of sampled cows.…”
Section: Effects Of Host Genetics and Rumen Microbiome In Milk Metabocontrasting
confidence: 83%
“…An exception to these reports was a higher heritability estimate reported by Buitenhuis et al (2013) for milk BHB (h 2 = 0.87) using cows that were all sampled in mid-lactation. The heritability value estimated in our study for milk acetone (h 2 = 0.10) was generally lower than estimates from previous studies, which were in the range of 0.22 to 0.31 (Lee et al., 2016; Ranaraja et al, 2018). Generally, heritability estimates for milk concentration of ketone bodies might vary between studies depending on stages of lactation of sampled cows.…”
Section: Effects Of Host Genetics and Rumen Microbiome In Milk Metabocontrasting
confidence: 83%
“…Koeck et al (2014) reported h 2 values ranging from 0.14 to 0.29 for Canadian Holsteins. Similar h 2 was reported for Korean Holsteins (Ranaraja et al 2018) ranging from 0.14 to 0.09 in the first and fourth parity, respectively. Weigel et al (2017) estimated heritability for three BHB phenotypes (maximum concentration, square root scale, binary scale) in Holsteins using both BLUP and ssGBLUP (0.06-0.09).…”
Section: Variance Components and Heritabilitiessupporting
confidence: 81%
“…Milk ketone body concentration, predicted from FTIR and collected during routine DHI testing, has been proposed as an indicator trait for HYK susceptibility. These traits are heritable, with milk acetone heritability ranging from 0.10 to 0.28 (van der Drift et al, 2012a;Ranaraja et al, 2018) and milk BHB heritability ranging from 0.067 to 0.19 (van der Drift et al, 2012a;Koeck et al, 2014;Jamrozik et al, 2016;Ranaraja et al, 2018). Genetic correlations between clinical HYK records and FTIR-predicted ketone bod-ies are moderate, ranging from 0.25 to 0.48 (Koeck et al, 2014;Jamrozik et al, 2016).…”
Section: Genetic and Genomic Management Of Ketosismentioning
confidence: 99%